A Bibliometric Study of Digital Franchise Models in Emerging Markets - Judijanto, Loso (The Es Economics and Entrepreneurship, 2025)
The rapid digital transformation across emerging markets has introduced new dynamics to franchising models, enabling innovative approaches that leverage technology, user experience, and scalable infrastructures. This study presents a comprehensive bibliometric analysis of scholarly literature on digital franchise models within these regions, using data from the Scopus database covering the period 2000–2024. Through VOSviewer, the study maps key trends in keyword co-occurrence, author collaboration, temporal evolution, and geographical distribution. Results reveal a multidisciplinary structure shaped by themes such as digital storage, human-computer interaction, transmedia, and design, with a recent rise in franchise-focused research. The United States, United Kingdom, and Australia emerged as dominant contributors, while countries like India and China show increasing participation. The findings provide valuable insights for academics, entrepreneurs, and policymakers by outlining the intellectual foundations of the field and identifying research gaps, particularly the need for context-specific studies and deeper integration of digital business theories. This study lays the groundwork for advancing a more inclusive, data-driven understanding of how franchising is evolving in digitally empowered but institutionally diverse economies.